Changing Trends of Vulvovaginal Candidiasis - Vijaya, Doddaiah; Dhanalakshmi, Tumkur Anjaneya; Kulkarni, Sunanda (Journal of Laboratory Physicians, 2014)
Introduction: Vulvovaginal candidiasis is one of the most common infections seen in women.Materials and Methods: A total of 300 symptomatic women were studied. High vaginal swabs collected from each patient were processed by Gram stain, culture on Sabourauds dextrose agar and CHROM agar plates. Isolates were identified and speciated using conventional methods and by the color of the colonies on the CHROM agar. Antifungal susceptibility was performed by disc diffusion method for fluconazole (25 μg) and voriconazole (1 μg) discs as per Clinical and Laboratory Standards Institute (CLSI) guidelines.Results: Vulvovaginal candidiasis was found in 53 (17.7%) of cases. Gram stain was positive in 22 (41.41%) of culture positives. Speciation of isolates by conventional and CHROM agar methods showed similar results. C. albicans 35 (66.0%) was the most common species isolated followed by C. tropicalis 14 (26.4%), C. krusei 2 (3.8%), C. parapsilosis and C. glabrata in 1 (1.9%) case each. Sensitivity to fluconazole was found in 91.4% of C. albicans, 57.1% of C. tropicalis and 50.0% of C. krusei. Sensitivity to voriconazole was seen in 91.4% of C. albicans, 85.7% of C. tropicalis and 50.0% of C. krusei. C. parapsilosis and C. glabrata were found sensitive only to voriconazole.Conclusion: CHROM agar has the advantage of being rapid, simple and cost effective method as compared to conventional methods in speciation of Candida. Routine susceptibility testing of Candida isolates help in selecting the most appropriate antifungal agent for vulvovaginal candidiasis.
Keywords: CHROM agar; fluconazole; voriconazole; vulvovaginal candidiasis